The Effectiveness of Government Regulation Number 48 of 2014 in Marriage Services at the KUA of Ampenan District: A Socio-Legal Study in Banjar Village - Muhammad Rifqi Jahroh; Siti Jahroh (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study examines the effectiveness of Government Regulation Number 48 of 2014 concerning Tariffs on Types of Non-Tax State Revenue Applicable to the Ministry of Religious Affairs, focusing on marriage service practices in Banjar Village, Ampenan District, Mataram City. The regulation stipulates a zero-rupiah tariff for marriages conducted at the Office of Religious Affairs and a Rp600,000 tariff for marriages conducted outside the office. This study aims to analyze the regulation of non-tax state revenue in marriage services, evaluate its implementation, and examine community responses to the policy. This research employed a qualitative method with a phenomenological approach. Data were collected through observation, interviews with officials of the Office of Religious Affairs, community leaders, neighborhood heads, and residents, as well as documentation of marriage records and relevant regulations. The findings show that Government Regulation Number 48 of 2014 is administratively effective because it has been implemented according to formal procedures, payments are made through official mechanisms, and no major problems related to gratuities were found. However, its social effectiveness remains limited. The data indicate that most residents of Banjar Village still prefer to conduct marriages outside the Office of Religious Affairs due to Sasak customary traditions, the need for family witnessing, limited office space and service time, and the desire to hold marriage ceremonies as communal events. Some residents consider the Rp600,000 tariff burdensome, especially when combined with customary expenses. This study confirms that legal effectiveness must be assessed through the relationship between state regulation, public service delivery, economic conditions, and local culture.